Compatible Behavior as an Actual Problem of Modernity - Serebryakova, T.A.; Koneva, I.A.; Egorova, T.E.; Kostina, O.A.; Tikhonina, S.A.; Khmelkova, E.V.; Sheshukova, N.N. (International Journal of Criminology and Sociology, 2022)
The article reflects the results of an empirical study in the field of the problem of coping behavior. Based on the research results of foreign and domestic scientists, we conclude that coping behavior is nothing more than a special purposeful socially-oriented behavior of a person, providing him with productivity, health and both psychological and social well-being. Considering that the formation of the experience of coping behavior is a prolonged and ongoing process throughout a person’s life, we determined the study of the specifics of coping behavior among students of higher educational institutions as the targets of our research. Moreover, as the main hypothesis of the study, we formulate an assumption about the dependence and conditionality of the experience of coping behavior on the age and training course of the respondents.